Investigation And Mitigation Of Harmonics Of Vfd (Case Study: In Wonji-Shoa New Sugar Factory, Ethiopia.) - Brihanu, H/Giorgis (ASTU, 2019)
Over, the last few decays, harmonic distortion in power supplies have increased significantly due to many electronic devices used in industry. This study focused on: one of these electronics device which is variable frequency drives (VFD) used for bagasse feeder??s application in wonji shoa sugar factory (WSSF). This drive produce harmonics because of variation in load pattern which must be suppressed the harmonics and improve the power factor using Distributed Static Compensator (DSTATCOM) device. In this thesis, the control strategy of DSTATCOM is synchronous reference frame theory based; It depends on DQ transformation, Phase Locked Loop (PLL) synchronization. The suggested method of filter design reduces harmonic distor
Keywords: DSTATCOM, Phase Locked Loop (PLL), VFDs, MATLAB/SIMULINK